ORBITAL CONGESTION COMPLICATING TREATMENT OF CEREBRAL VASCULAR ANOMALIES - Levin, Marc H. (2013)
BACKGROUND: The decision between conservative management and invasive treatment of juxtaorbital intracranial vascular anomalies can be challenging. Whereas arteriovenous malformations (AVMs) can lead to vision loss and are potentially life threatening if they rupture, invasive endovascular and surgical procedures also carry risks. CASE DESCRIPTIONS: Two patients developed blinding orbital congestion soon after successful treatment of cerebral vascular anomalies. The first patient, a 36 year-old man, underwent partial embolization followed by resection of a congenital frontal lobe AVM. The second patient, a 62 year-old woman, underwent embolization of a peri-orbital/skull base dural arteriovenous malformation. Following intervention, both patients developed unilateral vision loss proptosis, chemosis, complete ophthalmoplegia, and elevated intraocular pressure. The first patient suffered from acute orbital compartment syndrome in the absence of any acute localized hemorrhage or thrombosis. The second patient experienced refractory acute glaucoma from orbital congestion, secondary hyphema and angle closure due to superior ophthalmic vein and cavernous sinus thromboses. CONCULSIONS: These cases highlight the potential orbital congestion to worsen acutely after invasive treatment of juxtaorbital cerebral vascular anomalies, and suggest diverse mechanisms of resultant visual and orbital compromise. The first case represents the first report of orbital compartment syndrome following resection of a congenital AVM.